2021
DOI: 10.1088/1748-9326/ac3e20
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented acceleration of winter discharge of Upper Yenisei River inferred from tree rings

Abstract: The Yenisei River is the largest contributor of freshwater and energy fluxes among all rivers draining to the Arctic Ocean. Modeling long-term variability of Eurasian runoff to the Arctic Ocean is complicated by the considerable variability of river discharge in time and space, and the monitoring constraints imposed by a sparse gauged-flow network and paucity of satellite data. We quantify tree growth response to river discharge at the upper reaches of the Yenisei River in Tuva, South Siberia. Two regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 103 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…How streamflow in permafrost-dominated river basins responds to changes in temperature and precipitation along a climatic gradient is not fully understood. In addition, recent studies have found that the winter streamflow increased much faster than the annual streamflow in the permafrost-dominated upper river basins of Siberia (Panyushkina et al, 2021). Liu et al (2022) further revealed uneven increases in streamflow during early, mid-and late winter across four large Arctic river basins.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…How streamflow in permafrost-dominated river basins responds to changes in temperature and precipitation along a climatic gradient is not fully understood. In addition, recent studies have found that the winter streamflow increased much faster than the annual streamflow in the permafrost-dominated upper river basins of Siberia (Panyushkina et al, 2021). Liu et al (2022) further revealed uneven increases in streamflow during early, mid-and late winter across four large Arctic river basins.…”
Section: Introductionmentioning
confidence: 92%
“…Increased winter streamflow reveals that baseflow is increasing under a warming climate. Recent studies have indicated that accelerated permafrost warming and widespread forest fires in South Siberia are the two major drivers for increasing winter streamflow (Panyushkina et al, 2021). In continuous permafrost-dominated river basins, permafrost thaw is altering terrestrial hydrological processes by increasing the active-layer thickness and extending recession flow durations (Feng et al, 2022).…”
Section: Petmentioning
confidence: 99%
“…In recent decades an increase in freshwater runoff to the Arctic ocean (especially during the cold period of the year) has been observed for Eurasian (Stuefer et al, 2011;Shiklomanov et al, 2013;Tan and Gan, 2015;Déry et al, 2016;Tananaev et al, 2016) and North American (Shiklomanov and Lammers, 2011;Déry et al, 2016;Holmes et al, 2018) basins. However, recently observed trends in annual precipitation over these basins are not large enough to support this increase in runoff (Berezovskaya et al, 2004;Adam and Lettenmaier, 2008;Bring and Destouni, 2011;Bring et al, 2016;Panyushkina et al, 2021;Wang et al, 2021). On the other hand, the widespread increase in air temperature (Biskaborn et al, 2019) has been well documented.…”
Section: Introductionmentioning
confidence: 97%
“…This forcing is able to produce record-setting river discharge that is part of an accelerating trend (Shiklomanov and Lammers 2009). Although hydrological changes across and within river basins are heterogenous, the net effect is an increase in freshwater export to the Arctic Ocean in spring, summer and even winter (Panyushkina et al 2021;Feng et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Tree-ring records derived from conifers have been used to successfully extend discharge records across the pan-Arctic by hundreds of years (MacDonald et al 2007;Agafonov et al 2016). These studies provide critical insight not only into long-term annual discharge trends, but into seasonal trends as well (Panyushkina et al 2021). Dendrochronology of angiosperms offers an opportunity to fill even more of these gaps, particularly when it comes to capturing extreme hydrological events.…”
Section: Introductionmentioning
confidence: 99%